Peran Teknologi Pendidikan Dalam Pemanfaatan Pembelajaran IPS - Luluk Baikuna; M. Farhan Hidayatuloh; Muhammad Fikri Rizal; Nafiatul Fitria; Nurul Ulfatun Anjelina; M. Rivan Eko Mahendra; Marlina Marlina; Agustina Zahrotin Nisak (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The increasingly rapid development of information and communication technology (ICT) has had a significant impact on the world of education, global demands require the world of education to always adapt technological developments to efforts to improve the quality of education, especially in the Social Sciences learning process ( social studies). Teachers can utilize ICT to prepare the learning process and/or when the learning process takes place. With ICT teachers can add open materials and look for references about appropriate learning methods for their students. In learning, teachers can convey material more easily to students with the help of the use of ICT. The aim of writing this article is to understand the role of knowing information technology and educational communication in improving social studies learning. This article also discusses several challenges faced in integrating educational technology into social studies learning, such as unequal access to technology, inadequate curriculum, and teacher training needs, as well as how to overcome these challenges.